2011
DOI: 10.1002/mrd.22005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor alpha switches off secretory activity in the epididymal channel of the lizard Podarcis sicula

Abstract: The epididymis in the male reproductive tract allows the survival, viability, and storage of spermatozoa from the testis. In the lizard Podarcis sicula, the epididymis can be regionalized to an initial segment called the caput that comprises the efferent ductules, followed by the middle and terminal segments, respectively termed the corpus and cauda. By means of in situ hybridization and immunocytochemistry, we analyzed the expression of the estrogen receptors of the alpha and beta type (ERα and ERβ) in Podarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…The lumen of the cauda is empty during the nonreproductive season [15]. In Podarcis, we recently found that the expression of ER may act as a switch off for the secretory activity of the epididymal corpus [15]. Now by means of in situ hybridization (ISH) with the homologous Podarcis AR probe just obtained, it is demonstrated that in this lizard the AR expression is continuously present along the epididymis also in animals experimentally 2 International Journal of Zoology treated in the mating period with estradiol-17 (E 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The lumen of the cauda is empty during the nonreproductive season [15]. In Podarcis, we recently found that the expression of ER may act as a switch off for the secretory activity of the epididymal corpus [15]. Now by means of in situ hybridization (ISH) with the homologous Podarcis AR probe just obtained, it is demonstrated that in this lizard the AR expression is continuously present along the epididymis also in animals experimentally 2 International Journal of Zoology treated in the mating period with estradiol-17 (E 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this period the lumen is filled with spermatozoa and secretory granules that pass in the third region, cauda, whose epithelium does not show any changes throughout the year. The lumen of the cauda is empty during the nonreproductive season [15]. In Podarcis, we recently found that the expression of ER may act as a switch off for the secretory activity of the epididymal corpus [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations